2009
DOI: 10.1016/j.neuroimage.2009.04.073
|View full text |Cite
|
Sign up to set email alerts
|

A review of neuroimaging studies of stressor-evoked blood pressure reactivity: Emerging evidence for a brain-body pathway to coronary heart disease risk

Abstract: An individual's tendency to show exaggerated or otherwise dysregulated cardiovascular reactions to acute stressors has long been associated with increased risk for clinical and preclinical endpoints of coronary heart disease (CHD). However, the 'brain-body' pathways that link stressor-evoked cardiovascular reactions to CHD risk remain uncertain. This review summarizes emerging neuroimaging research indicating that individual differences in stressor-evoked blood pressure reactivity (a particular form of cardiov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
125
1
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 228 publications
(340 reference statements)
10
125
1
4
Order By: Relevance
“…The findings of the present systematic review and other studies on HRV and functional brain imaging are consistent with research on the brain areas implicated in stressorevoked blood pressure reactivity [25]. Those studies indicated that the insula, cingulate cortex, and amygdala are the core components implicated in the blood pressure responses to stress.…”
Section: Systematic Reviewsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of the present systematic review and other studies on HRV and functional brain imaging are consistent with research on the brain areas implicated in stressorevoked blood pressure reactivity [25]. Those studies indicated that the insula, cingulate cortex, and amygdala are the core components implicated in the blood pressure responses to stress.…”
Section: Systematic Reviewsupporting
confidence: 89%
“…Those studies indicated that the insula, cingulate cortex, and amygdala are the core components implicated in the blood pressure responses to stress. Blood pressure responses were also related to altered rCBF or BOLD signal changes in the medial, lateral, and dorsal prefrontal cortices, the parietal cortex, occipital cortex, somatosensory cortex, cuneus, lentiform area, caudate, thalamus, and cerebellum [25]. Interpretation and generalisation of the results of the present systematic review and other summary articles in this area are complicated by methodological differences, the potential of statistical type I error related to the analysis of multiple brain structures, and the relatively small number of studies that simultaneously assessed cardiovascular measures and brain responses to psychological distress.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Among the brain areas most consistently related in previous work to stressor‐evoked cardiovascular reactivity—as well as some markers of autonomic cardiovascular control, inflammation, and arterial markers of preclinical vascular disease—are areas within the medial prefrontal cortex, anterior cingulate cortex, insula, extended amygdala, hippocampus, and hindbrain and brainstem cell groups 1, 13, 16. It has been proposed that signaling patterns between these areas may serve to calibrate the magnitude of physiological (eg, cardiovascular) reactions to anticipated self‐relevant demands (eg, stressors) to support contextually adaptive behavioral coping processes 13, 46, 47. Moreover, an individual's propensity to exhibit “ mis ‐calibrations” between brain and physiological activity may reflect a dimension of individual difference that underlies the expression of “exaggerated” (metabolically excessive or pathophysiological) autonomic, inflammatory, and cardiovascular reactions, including stressor‐evoked BP reactions that have been linked to preclinical CVD 46, 47, 48.…”
Section: Discussionmentioning
confidence: 99%
“…Combined with behavioral research showing that lower-status individuals tend to be more engaged during social interactions (Kraus and Keltner, 2009) and are better at reading the emotions of others (Kraus et al, 2010), these patterns suggest that DMPFCrelated attention to others' thoughts and feelings may also track with lower perceived social status. The DMPFC has strong connections with the amygdala and other brainstem regions whose activity can drive stress-related changes in the cardiovascular system and the hypothalamic-pituitary-adrenal axis (Gianaros and Sheu, 2009;Eisenberger and Cole, 2012;Muscatell and Eisenberger, 2012), and as such, it is possible that the DMPFC may also play a key role in linking social status and inflammation. To date, however, no known research has tested this possibility.…”
Section: Introductionmentioning
confidence: 99%